Integrasi Literasi Kesehatan Digital dan Artificial Intelligence dalam Meningkatkan Perilaku Preventif Masyarakat - Rafi Pratama Nugraha; Sinta Maharani Putri; Fikri Aditya Saputra (Gema Cendekia Institute, 2026)
The rapid development of digital technology and Artificial Intelligence (AI) has transformed the way people access, understand, and utilize health information. The integration of digital health literacy and AI has become increasingly important in supporting preventive health behaviors amid the growing prevalence of non-communicable diseases and the spread of health misinformation. This study aims to analyze the relationship between digital health literacy and AI utilization in improving preventive health behavior through a systematic literature review approach. The study examined 25 international scientific articles published between 2013 and 2026 from reputable academic databases. Thematic analysis was employed to identify patterns linking digital health literacy, AI utilization, health empowerment, health communication, and preventive behavior. The findings indicate that the integration of digital health literacy and AI significantly improves access to health information, personalizes health education, enhances decision-making abilities, and strengthens individuals’ self-efficacy in adopting preventive behaviors. AI-based technologies such as health chatbots, recommendation systems, telemedicine platforms, and adaptive learning applications have demonstrated effectiveness in increasing user engagement in disease prevention activities. However, challenges related to digital inequality, data privacy, algorithmic bias, and limited AI literacy remain significant barriers. The study concludes that strengthening both digital health literacy and AI literacy simultaneously is a strategic approach to promoting sustainable preventive health behavior among communities.